Penerapan Pembelajaran Problem Based Learning Untuk Meningkatkan Hasil Belajar Siswa Kelas V SDN Triwung Kidul 1 - Anjarwati, Ani; Jannah, Amalia Hikmatul; Romla, Siti; Faruqi, Moch. Umar Al; Ferdiansyah, Dandi (Jurnal Pendidikan, Sains Dan Teknologi, 2022)
The researcher chose the PBL (Problem Based Learning) learning model. One learning model that provides opportunities for students to have experience discovering a concept and developing critical thinking skills. This study aims to describe the application of the PBL (Problem Based Learning) learning model in improving the learning outcomes of elementary school students. In more detail, this study aims to describe the implementation of learning by applying the PBL (Problem Based Learning) learning model to improve the learning outcomes of fifth grade students at SDN Triwung Kidul 01 and to describe the improvement in student learning outcomes after applying the PBL (Problem Based Learning) learning model. The learning outcomes test is used to obtain information on students' initial abilities before the learning process and students' mastery of the material being taught. Data collection techniques are carried out by observation, tests and documentation on the implementation of the learning process with the Problem Based Learning (PBL) learning model. Implementation of the learning process by applying the Problem Based Learning model can help students understand concepts or learning materials well, draw conclusions and find answers to existing questions.